A Model of Perceived Co-creation Value in Tourism Service Setting: An Application of Structure Equation Modeling - Tao, Kefang; Ye, Jiangeng; Xiao, Hanjie; Chen, Poju (Frontiers in Psychology, 2022)
This study explores how the perceived co-creation values (PCVs) from tourists’ perspectives are applied in the customized tour arrangement service setting. The sequential qualitative and quantitative methods are adopted for this study. The initial qualitative method in terms of the proactive semi-structured interview is conducted to identify and explore the dimension of the PCV construct and to develop its measurement scale. The quantitative method by the structure equation model is employed for the proposed conceptual model fitness assessment and consolidation. Our work contributes to the progression of value co-creation research in a customized tourism context and provides a valid and reliable PCV instrument to tourism practitioners for a better service platform designing. The mediating role of customer satisfaction (CS) between PCV and customer loyalty (CL) offers service providers a deeper understanding of customer psychology and behavior, and thus, the loyal customer cultivation strategy.